A romániai Bánság fejlettsége a Dél-Alfölddel történő összevetésben - Keczer, Gabriella; Czagány, László (Közép-Európai Közlemények, 2010)
In our paper we compare the state of development of the Romanian statistical (EU NUTS II. level) region called Vest with the Hungarian statistical region called Dél-Alföld. We do so because the Vest region includes and almost exclusively consists of the historic Banat, and statistical data is available only for statistical, and not for geographical or historical units. We compare three groups of data: data showing the economic state of development, data concerning employment and labor market, and data related to education and science. Our research is based on the data of Eurostat. Generally we can conclude that in static indicators (showing the current state of development such as the present level of GDP or income, the number of people having a degree) Dél-Alföld seems to be in a better position, but in dynamic indicators (showing the pace of development such as the growth of GDP or income, the number of students) the Vest region is well ahead.